A Prospective Study on Building Quality: Relationship between Workmanship Quality and Common Building Defects of Low-cost Construction Projects - Othuman Mydin, M.A.; Othman, N.A.; Sani, N. Md. (EDP Sciences, 2014)
This study focuses on the quality of workmanship in the construction of lowcost housing in Kedah and Penang State, Malaysia and its relation to defects occurring in the building. The objectives of this study are to investigate common building defects that mostly occur at low-cost housing due to poor workmanship, the factors that contribute to poor workmanship and to established possible measures to minimize these problems. From the combination of literary reviews and questionnaire surveys, this research explores all the stated objectives. For this particular study, quantitative research was conducted through questionnaire surveys involving respondents who are involved in and are experienced in working on construction projects. After analysing the data, this study found that most common defects occurring on low-cost housing are cracks on walls, settlement and peeling paint. Additionally, construction of low-cost housing commonly suffers from low quality workmanship due to poor project management and a lack of experience and competency among labourers. These significant impediments can be remedied by providing training and education to the labourers as well as implementing strict supervision during construction work.